Fostering Well-Being in Education Through Yoga and Mindfulness in the Snow (Snowga) (LEARNing Landscapes, 2017)
Through a program called Snowga (yoga in the snow), students learned about mindfulness and living in the present moment through yoga postures and meditations. Positive changes included growth in wellbeing as the children explored self, community, and the natural world through yoga, mindfulness, personal reflective journals, and artwork. The purpose: to engender awareness of the efficacy of mindfulness and yoga practices in nature and contribute to the growing body of knowledge around wellbeing in education.
Keywords: Snowga (yoga in the snow); yoga; mindfulness; well-being; education